Exploring pain science education in the context of a healthcare dyad: what supports or hinders pain reconceptualisation? - Le Roux, Stian (Department of Psychiatry and Mental Health, 2025)
Background. Pain Science Education (PSE) has emerged as a useful treatment strategy for a wide range of painful conditions, including persistent musculoskeletal pain (PMP). The interaction between the two members of a healthcare dyad is subject to various contextual elements. It remains unclear which contextual elements within the PSE dyadic interaction help or hinder the recipient's reconceptualisation of pain. Purpose of the Study. The purpose of the study was to explore and understand participants' experiences of a PSE intervention and elicit perspectives of a PSE dyad relating to elements of their interaction that supported or hindered the reconceptualisation of pain. Methodology. This study employed a phenomenological research design. Semi-structured interviews were conducted with eight PSE dyads – healthcare providers and people under their care (n = 17). An interpretive phenomenological analysis framework was used to analyse and interpret the data. Summary of Qualitative Findings. Dyad members had mostly congruent perspectives on elements that supported reconceptualisation, especially a strong therapeutic alliance. Some intra-dyadic incongruencies included recipient pain beliefs, which some PSE recipients believed supported reconceptualisation, while their providers perceived them as a barrier. A common thread that influenced multiple contextual elements, was pain intensity. Pain relief was often identified as a helpful element as it increased trust in the provider and the PSE. Increased pain was an unhelpful element for some PSE recipients, but their PSE providers found that it helped reconceptualisation, considering it a learning opportunity. This was another area where intra-dyadic perspectives were incongruent. A novel insight included the value of experiential PSE, where providers facilitated reflection and discussion of painful sensations and experiences, with the explicit goal of deepening the learning by exploring pain as a sensory-affective experience. Observing other painful conditions was another learning avenue that dyads valued, where observation of other pain presentations could be compared with their own experience to gain a deeper understanding of pain. Conclusion. Exploring the perspectives of both members of a PSE dyad triangulated the meaning that each member made of the contextual elements that influenced reconceptualisation, drawing out the similarities and differences in their perspectives. PSE dyads valued a range of contextual elements, and dyadic perspectives mostly converged on the theme that PSE is built on a strong therapeutic alliance and a skilled PSE provider. A limitation of this study was that the selection bias was oriented toward participants with positive PSE experiences. This new perspective of elements that influence reconceptualisation may inform PSE implementation and increase its effectiveness.